The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.7454/nrjs.v4i1.62
|View full text |Cite
|
Sign up to set email alerts
|

Duration and frequency of catheterization in central vein stenosis: A case control study

Abstract: Introduction. Placement of the central vein catheterization (CVC) is a major risk factor for central vein stenosis (CVS). Repetitive endothelial exposures to the CVC results in inflammation, microthrombi formation, hyperplasia of the intima, fibrosis and thus development of CVS. The study aimed to find out the correlation between the duration and frequency of CVC in patients with CVS. Method. A matched case-control study was conducted in dr. Cipto Mangunkusumo General Hospital. Samples were taken from the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…4 The prevalence of central venous stenosis in America was by 29%, for Cipto Mangunkusumo hospital was by 7.53%, while in Pelni hospital prevalence rate was by 13.5%. 7 Previous studies revealed that the mortality rate was 4 times higher in patients with renal failure when surgery was performed. This is due to the comorbid conditions that accompany patients with renal failures, such as systemic arteriosclerosis, chronic inflammation, malnutrition.…”
Section: Case Reportmentioning
confidence: 99%
“…4 The prevalence of central venous stenosis in America was by 29%, for Cipto Mangunkusumo hospital was by 7.53%, while in Pelni hospital prevalence rate was by 13.5%. 7 Previous studies revealed that the mortality rate was 4 times higher in patients with renal failure when surgery was performed. This is due to the comorbid conditions that accompany patients with renal failures, such as systemic arteriosclerosis, chronic inflammation, malnutrition.…”
Section: Case Reportmentioning
confidence: 99%
“…Clinical manifestations include pain; superior extremities and facial edema; dilatation of collateral veins in the face, neck, and chest; tissue damage and ulceration. 5 The incidence of CVS in the population routinely undergoing HD is 14% in the United States, and in Canada is 23%-29%, but the data have not been obtained in Indonesia. 6 The risk factors for CVS include the location of the CVC, the type and material of the catheter, the length of time the catheter was inserted, a history of the previous CVC placement, and a long duration of catheter insertion (> 6 weeks).…”
Section: Introductionmentioning
confidence: 99%